T-cell receptor transfer for boosting HIV-1-specific T-cell immunity in HIV-1-infected patients. (10th September 2016) - Mummert, Christiane; Hofmann, Christian; Hückelhoven, Angela G.; Bergmann, Silke; Mueller-Schmucker, Sandra M.; Harrer, Ellen G.; Dörrie, Jan; Schaft, Niels; Harrer, Thomas
Abstract : Objectives: Strategies to cure HIV-1 infection require the eradication of viral reservoirs. An innovative approach for boosting the cytotoxic T-lymphocyte response is the transfer of T-cell receptors (TCRs). Previously, we have shown that electroporation of TCR-encoding mRNA is able to reprogram CD8 + T cells derived from healthy donors. So far, it is unknown whether the transfer of HIV-1-specific TCRs is capable to reprogram CD8 + T cells of HIV-1-infected patients. To assess the efficiency of TCR-transfer by mRNA electroporation and the functionality of reprogramed T cells in HIV-1-infected patients, we performed an in-vitro analysis of TCR-transfer into T cells from HIV-1-infected patients in various stages of disease and from healthy controls. Methods: Peripheral blood mononuclear cells from 16 HIV-1-infected patients (nine HLA-A * 02-positive, seven HLA-A * 02-negative) and from five healthy controls were electroporated with mRNA-constructs encoding TCRs specific for the HLA-A * 02/HIV-1-gag p17 epitope SLYNTVATL (SL9). Functionality of the TCRs was measured by γIFN-ELISpot assays. Results: SL9/TCR transfection into peripheral blood mononuclear cells from both HLA-A * 02-positive and HLA-A * 02-negative HIV-1-infected patients and from healthy blood donors reprogramed T cells for recognition of SL9-presenting HLA-A * 02-positive cells in γIFN-ELISpot assays. SL9/TCR-transfer into T cells from an immunodeficient AIDS patient could induce recognition of SL9-expressing target cells only after reversion of T-cell dysfunction by antiretroviral therapy. Conclusion: The transfer of HIV-1-p17-specific TCRs into T cells is functional both in HIV-1-infected patients as well as in healthy blood donors. TCR-transfer is a promising method to boost the immune system against HIV-1. Abstract : Supplemental Digital Content is available in the text